Strategi Komunikasi Politik Tim Kampanye Daerah Joko Widodo – K.H. Ma’ruf Amin Provinsi Jawa Timur dalam Pemenangan PILPRES 2019 - Dafis Ubaidillah Assiddiq; Dewi Ambarwati (Universitas Merdeka Malang, 2021)
This study aims to discuss how the Regional Campaign Team (TKD) Ir. Joko Widodo - KH. Ma'ruf Amin of East Java Province in formulating the strategy of the East Java TKD funds of local officials, Jokowi's volunteer network and East Java kyais and political figures to win the Candidate Candidate No.1.In this study several resource persons stated that the role of all elements of society and figures and clerics and in the 2019 presidential election were very compact and effective, especially with the many issues of ethnicity, race and religion, which were used to attack incumbent Joko Widodo. This type of research uses descriptive qualitative methods and case study methods, with data collection techniques, namely interviews and documentation. The purpose of this research is to describe the Strategy of the East Java Regional Campaign Team Joko Widodo - KH. Ma'ruf Amin and Jokowi Volunteers during the Presidential election, therefore the East Java TKD strategy is an opinion leader to determine the Getter vote and become a political mediator to various parties who have an important role to increase votes in East Java. Keywords: Regional Campaign Team, Political Strategy, Presidential Election